Smart Services: Artificial Intelligence in Service Systems - Amorim, Marlene; Cohen, Yuval; Reis, João (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This special issue contains 11 papers dealing with various aspects related to the usage of artificial intelligence in service provision. The Special Issue includes a broad range of papers covering recent applications of AI and new technologies across service businesses. The papers cover managerial and customer challenges, technologies, service robotics and research trends. Overall, the Special Issue offers knowledge for advancing the adoption of AI in services and inspiring managerial decisions and innovation in the fields of: service systems, smart service, service digitization, customer interactions, artificial intelligence, emotion detection, servitization, service robots and digitalization.